Cirkulišući biomarkeri homocisteina, oksidativnog stresa i imunoglobulina kao prediktori postoperativne disfunkcije površine oka kod starijih pacijenata sa kataraktom: Serum Biomarkers Predict Postoperative Dry Eye - Wang, Yenan; Wang, Xizhe; Li, Zhen; Zhang, Lu; Yang, Huiqing; Zhang, Xuxiang (Journal of Medical Biochemistry, 2026)
Background: Postoperative dry eye is a frequent complication following cataract surgery in elderly patients. Increasing evidence suggests that systemic metabolic imbalance, oxidative stress, and immune dysregulation contribute to ocular surface dysfunction. This study aimed to investigate the predictive value of circulating biochemical biomarkers, including homocysteine (Hcy), oxidative stress indicators, and immunoglobulin levels, for postoperative dry eye.Methods: A total of 174 elderly patients undergoing phacoemulsification with intraocular lens implantation between January 2024 and November 2025 were retrospectively analyzed. Patients were divided into a postoperative dry eye group (n = 76) and a control group (n = 98). Preoperative serum levels of homocysteine (Hcy), superoxide dismutase (SOD), interleukin-6 (IL-6), and immunoglobulins (IgA, IgG, IgM) were measured. Univariate and multivariate logistic regression analyses were used to identify independent biochemical predictors of postoperative dry eye. Receiver operating characteristic (ROC) curves were used to evaluate the predictive performance of individual and combined biomarkers.Results: Patients who developed postoperative dry eye exhibited significantly higher serum Hcy and IL-6 levels and lower SOD, IgA, and IgG levels compared with controls (P < 0.05). Multivariate logistic regression identified elevated Hcy (OR = 1.325), elevated IL-6 (OR = 1.568), decreased SOD (OR = 0.972), and decreased IgG (OR = 0.856) as independent predictors of postoperative dry eye (P < 0.05). ROC analysis demonstrated that the combined biomarker model achieved superior predictive performance (AUC = 0.915) compared with individual biomarkers.Conclusions: Circulating homocysteine, oxidative stress, and immune biomarkers are closely associated with postoperative dry eye in elderly cataract patients. Combined assessment of Hcy, SOD, IL-6, and IgG provides a promising biochemical approach for preoperative risk stratification and early identification of patients at high risk for postoperative ocular surface dysfunction.